Incidental Emotions and Hedonic Forecasting: The Role of (Un)certainty - Polyportis, Athanasios; Kokkinaki, Flora; Horváth, Csilla; Christopoulos, Georgios (Frontiers in Psychology, 2020)
The impact of incidental emotions on decision making is well established. Incidental emotions can be differentiated on several appraisal dimensions, including certainty-uncertainty. The present research investigates the effect of certainty-uncertainty of incidental emotions on hedonic forecasting. The results of four experimental studies indicate that uncertainty associated incidental emotions, such as fear and hope, compared with certainty emotions, such as anger and happiness, amplify predicted utility. This amplification effect is confirmed for opposite utility types; uncertainty associated emotions, when compared with their certainty counterparts, lead to an overprediction of positive utilities and to an underprediction of negative utilities. In line with the Appraisal-Tendency Framework (Lerner and Keltner, 2000; 2001), this effect is mediated by the prediction task uncertainty, providing evidence for a carryover process of the incidental emotion. The effect of task uncertainty on predicted utility is, in turn, partly mediated by attention to the task, suggesting that an affective adaptation process (AREA model; Wilson & Gilbert, 2008) lies behind the amplification of forecasts. Taken together, these findings extend the impact of certainty-uncertainty to the context of hedonic forecasting and further corroborate the impact of incidental emotions in judgement and decision making.